2015
DOI: 10.1103/physrevlett.115.130402
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioThermodynamic Results for the Degenerate Electron Gas at Finite Temperature

Abstract: The uniform electron gas (UEG) at finite temperature is of key relevance for many applications in dense plasmas, warm dense matter, laser excited solids and much more. Accurate thermodynamic data for the UEG are an essential ingredient for many-body theories, in particular, density functional theory. Recently, first-principle restricted path integral Monte Carlo results became available which, however, due to the fermion sign problem, had to be restricted to moderate degeneracy, i.e. low to moderate densities … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
209
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(220 citation statements)
references
References 53 publications
11
209
0
Order By: Relevance
“…However, to nevertheless obtain accurate QMC results at WDM conditions, we have introduced two novel QMC methods that are efficient at complementary parameter regimes. The CPIMC method [12,13] is formulated in anti-symmetric Fock-space and can be interpreted as a Monte Carlo simulation of the exact, infinite perturbation expansion around the ideal (non-interacting) system. Therefore, it excels at strong degeneracy and high density, but becomes inefficient towards strong coupling.…”
Section: Hamiltonian In Second Quantizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to nevertheless obtain accurate QMC results at WDM conditions, we have introduced two novel QMC methods that are efficient at complementary parameter regimes. The CPIMC method [12,13] is formulated in anti-symmetric Fock-space and can be interpreted as a Monte Carlo simulation of the exact, infinite perturbation expansion around the ideal (non-interacting) system. Therefore, it excels at strong degeneracy and high density, but becomes inefficient towards strong coupling.…”
Section: Hamiltonian In Second Quantizationmentioning
confidence: 99%
“…[10,11] It was only recently that the combination of two novel methods (configuration path integral Monte Carlo [CPIMC] [12,13] ) and permutation blocking path integral Monte Carlo [PB-PIMC] [14,15] ) that are available at complementary parameter ranges allowed to conduct the first unbiased simulation of the UEG. At first, these efforts were limited to a finite number of electrons N in a finite simulation cell of volume V. [16,17] In practice, however, one is interested in the thermodynamic limit, which is given by the limit of an infinite number of particles at fixed density (or, equivalently, fixed r s ).…”
Section: Introductionmentioning
confidence: 99%
“…[22]) we have combined two novel complementary approaches: our configuration path integral Monte Carlo (CPIMC) method [23][24][25] excels at high to medium density and arbitrary temperature, while our permutation blocking path integral Monte Carlo (PB-PIMC) approach [26,27] significantly extends standard fermionic PIMC [28,29] towards lower temperature and higher density. Surprisingly, it has been found that existing RPIMC results are inaccurate even at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…An independently developed third approach, density matrix QMC [40,41], confirmed the excellent quality of these results. The only significant errors remaining are finite-size effects [37,[42][43][44][45][46], which arise from the difference between the small systems simulated and the infinite [thermodynamic limit (TDL)] system of interest.…”
mentioning
confidence: 99%
“…Recently, we were able to show [32][33][34] that accurate simulations of these systems are possible over a broad parameter range without any nodal restriction. Our approach combines two independent methods, configuration path-integral Monte Carlo (CPIMC) [35][36][37] and permutation blocking PIMC [38,39], which allow for accurate simulations at high (r s 1) and moderate densities (r s 1 and θ 0.5), respectively. An independently developed third approach, density matrix QMC [40,41], confirmed the excellent quality of these results.…”
mentioning
confidence: 99%